Factors influencing the adoption of mHealth services in a developing country: A patient-centric study. (February 2020) - Alam, Mohammad Zahedul; Hoque, Md. Rakibul; Hu, Wang; Barua, Zapan
Highlights: mHealth is one of the promising technologies that contributes a considerable value in delivering health care services. This study investigates the factors affecting the adoption intention and use of mHealth services in a developing country. This study proposes a comprehensive conceptual model that clarifies the use of mHealth services. The model developed can be easily modified to investigate the adoption of mHealth services in other developing countries. Abstract: mHealth under the umbrella of eHealth has become an essential tool for providing quality, accessible and equal health care services at an affordable cost. Despite the potential benefits of mHealth, its adoption remains a big challenge in developing countries such as Bangladesh. This study aims to examine the factors affecting the adoption of mHealth services in Bangladesh by using the extended Unified Theory of Acceptance and Use of Technology (UTAUT) model with perceived reliability and price value factors. It also examines the moderating effect of gender on the intention to use and on the actual usage behavior of users of mHealth services. A well-structured face-to-face survey was employed to collect the data. Structural equation modeling (SEM) with a partial least squares method was used to analyze the data collected from 296 generation Y participants. The results confirmed that performance expectancy, social influence, facilitating conditions and perceived reliability positively influence the behavioral intention to adopt mHealth services. However, effort expectancy and price value did not have a significance influence on the behavioral intention. Moreover, Gender has a significant moderating effect on mHealth services adoption in certain cases. Finally, the theoretical and practical implications of this study are also discussed.